Association between age and efficacy of combination systemic therapies in patients with metastatic hormone-sensitive prostate cancer: a systematic review and meta-analysis - Rajwa, Pawel; Yanagisawa, Takafumi; Heidegger, Isabel; Zattoni, Fabio; Marra, Giancarlo; Soeterik, Timo F W; van den Bergh, Roderick C N; Valerio, Massimo; Ceci, Francesco; Kesch, Claudia V; Kasivisvanathan, Veeru; Laukhtina, Ekaterina; et al. (Prostate cancer and prostatic diseases, 2023)
BACKGROUND: Combination systemic therapies have become the standard for metastatic hormone-sensitive prostate cancer (mHSPC). However, the effect of age on oncologic outcomes remains unknown. Our aim was to perform a systematic review, meta-analysis, and network meta-analysis (NMA) on the effect of chronological age on overall survival (OS) in patients treated with combination therapies for mHSPC. METHODS: We searched the PubMed®, Web of ScienceTM, and Scopus® databases to identify randomized controlled trials (RCTs) that analyzed the efficacy of combination systemic therapies using ADT plus docetaxel and/or androgen receptor signaling inhibitor (ARSI) in patients with mHSPC. We included studies, which provided separate hazard ratios (HRs) for younger vs. older patients. The selected age cut-off was 70 years (±5 years). Our outcome of interest was OS. RESULTS: We included nine RCTs with a total of 9183 patients. Younger and older men constituted 51% and 49% of included patients, respectively. Docetaxel plus ADT significantly improved OS among both older (HR 0.79, 95% CI 0.63-0.99, p = 0.04) and younger patients (HR 0.79, 95% CI 0.69-0.90, p < 0.001) with no differences according to age. ARSI plus ADT improved OS in older (HR 0.72, 95% CI 0.64-0.80, p < 0.001) and younger (HR 0.58, 95% CI 0.51-0.66, p < 0.001) patients; younger patients did benefit more (p = 0.02). On NMA treatment ranking, triplet therapy showed the highest probability of OS benefit irrespective of age group; in older patients, the benefit of triplet therapy compared to doublet was less expressed. CONCLUSIONS: Patients with mHSPC benefit from combination systemic therapies irrespective of age; the effect is, however, more evident in younger patients. Chronological age alone seems not to be a selection criteria for the administration of combination systemic therapies.
Keywords: antagonisté androgenů; Hormones; Male; lidé; Aged; Androgen Antagonists; Docetaxel; mužské pohlaví; hormony; docetaxel; Humans; Antineoplastic Combined Chemotherapy Protocols; nádory prostaty; protokoly protinádorové kombinované chemoterapie; Prostatic Neoplasms; senioři